Socio-economic and demographic factors of crime in Germany: evidence from panel data of the German states - Horst Entorf; Hannes Spengler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1998)
Our study is based on the traditional Becker-Ehrlich deterrence model, but we analyse the model in the face of currently discussed factors of crime like demographic changes, youth-unemployment and income inequality. We use a panel of the German Laender (states) that allows us to exploit different experiences in densely and sparsely populated areas as well as in East and West Germany. Our results are based on static and dynamic panel econometrics/criminometrics. They confirm the deterrence hypothesis for crime against property. Only weak support can be observed for crime against the person. Economic and demographic factors reveal important and significant influences. Being young and unemployed increases the probability of committing crimes.
Keywords: J19; K42; 330; Crime; deterrence; socio-economic factors; demographics; income opportunities; panel data; Kriminalitätsökonomik; Bevölkerungsdichte; Jugendarbeitslosigkeit; Einkommensverteilung; Schätzung; Deutschland